The Management of Conflict Resolution On Labor Wages - Sarwani, Sarwani; Anggraeni, RR Dewi; Rezki, Annissa (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Every job that utilizes services and human resources certainly require a salary for payment. This fee will be used to fulfill the necessities of life, both for the personal needs of workers, and other needs including household necessities. However, it is undeniable that in the reality of granting wage, it often experiences some obstacles, either caused by workers or from the company itself. Consequently, this creates a conflict that requires resolution. Therefore, it is necessary to manage this conflict resolution of labor or workers' earning according to the Indonesian labor law. This study applied qualitative research methods with literature and empirical approach. Data are collected through the analysis of legislation and the phenomenon that occurred in real life. The results of the study revealed that there are still many conflicts overpayment of labor wages, so the companies have to apply labor salary management based on applicable regulations. Thus, it is necessary to practice the resolution of disputes in this matter maximally, particularly related to the provision of a reasonable wage between the workers and the company.Keywords: Conflict Resolution, Labor Wages, Companies Abstrak:Setiap pekerjaan yang menggunakan jasa dan tenaga manusia sudah pasti membutuhkan upah untuk pembayarannya. Upah inilah yang nantinya akan digunakan untuk memenuhi kebutuhan hidup, baik pribadi pekerja, maupun kebutuhan lainnya termasuk kebutuhan rumah tangga. Namun tidak dapat dipungkiri bahwa dalam realita pemberian hak upah, kerap mengalami kendala, baik yang disebabkan dari buruhnya maupun dari pihak perusahaan pemberi upah. Sehingga hal ini menimbulkan konflik yang membutuhkan penyelesaian. Oleh karenanya dibutuhkan manajemen penyelesaian konflik sengketa pemberi upah buruh atau pekerja ini, dengan didasarkan undang-undang ketenagakerjaan Republik Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan literatur dan empiris. Data yang didapat melalui analisis peraturan perundang-undangan dan fenomena yang terjadi di lapangan. Hasil penelitian menyatakan bahwa masih terdapat banyak konflik pembayaran upah buruh, sehingga perusahaan harus mampu menerapkan manajemen pemberian upah layak buruh yang didasarkan aturan yang berlaku. Oleh Karena itu perlu dilakukannya praktik penyelesaian sengketa dalam persoalan ini secara maksimal, khususnya terkait pemberian upah yang layak antara pihak buruh dan perusahaan.Kata kunci: Penyelesaian Sengketa, Upah Buruh, Perusahaan АннотацияКаждая работа, которая использует услуги и человеческие ресурсы, безусловно, требует заработную плату. Эта заработная плата будет использоваться для удовлетворения жизненных потребностей как для личных нужд работников, так и для других нужд, в том числе бытовых. Однако, нельзя отрицать, что в реальности, предоставление заработной платы часто сталкивается с некоторыми препятствиями, вызванными либо работниками, либо самой компанией. Следовательно, это создает конфликт, который требует разрешения. Вследствие этого, необходимо управлять урегулированием конфликтов разногласий по оплате труда в соответствии с индонезийским трудовым законодательством. В этом исследовании применялись качественные методы исследования с литературным и эмпирическим подходом. Данные собираются путем анализа законодательства и явлений, которые произошли в реальной жизни. Результаты исследования показали, что по-прежнему существует много конфликтов по поводу выплаты заработной платы, поэтому компаниям приходится применять управление надлежащей заработной платы на основе применимых норм. Таким образом, необходимо максимально применять урегулирование разногласий в этом вопросе, особенно связанных с предоставлением надлежащей заработной платы между работниками и компанией.Ключевые слова: Урегулирование конфликтов, Трудовая заработная плата, Компания